Premium burger patty: Mc'shameer / Muhammad Al-Hadi ...[et al.] - Rusli, Muhammad Al-Hadi; Nasaruddin, Muhammad Luqman; Zulkifli, Muhammad Eizuddin Hamzah; Salehudin, Shahmeer Irfan (2022)
For this grouping assignment, we need to make our own business plan to learn on how to become an entrepreneur in a group by managing our own business and make a planning to make our business happen. That is why we decided to be selling a Premium Patty Burger. We want to compete with existing patty product. We decided to name our company as Mc’Shameer the Premium Patty Burger. In recent years, there has been an increased demand for high-quality, delicious burgers. Our company has spent months researching and developing a recipe that we believe will be a hit with customers. We have tested our burgers with a focus group and the feedback was overwhelmingly positive. The main purpose of this business is to make a high-quality patty burger. We also want to make a variety type of patty burger. For example, not only make a meat cow, but also we want to make a meat from rabbit meat, goat meat, deer meat and etc. Not like others product that are selling only just one or two varieties of meat. For the location of our factory is we decided to open factory at Pasir Gudang, Johor. This is because this place is surrounded by other known and popular factory. So, our company name can grow fast. The reasons why are we make this business is because we want to fulfil our customers’ needs. Other product might be low-quality patty burgers and we want to improve that. Our patty burgers are made with 100% beef and a unique blend of spices. They are cooked to perfection, ensuring that they are juicy and flavorful. Each patty is approximately 1/3 pound, making them a substantial meal. We use only the freshest ingredients, including locally sourced produce when possible. Our target market is anyone who loves a good burger. We believe that our patty burgers will be popular with a wide range of customers, including families, young adults, and older adults. We will be targeting both sit-down restaurants and fast-food outlets to make our product available to as many people as possible.